Paracentral acute middle maculopathy with occlusive retinal vasculitis in presumed intraocular tuberculosis and hyperhomocysteinemia. Issue 11 (11th November 2022) - Samanta, Ramanuj; Dogra, Mohit; Puthalath, Athul Suresh; Sood, Gitanjli
Abstract : A male patient presented with a sudden visual decline in the right eye (OD). Fundus revealed bilateral vasculitis; OD also showed an occluded inferior retinal vein and a wedge-shaped retinal opacification of the inferior macula and nasal retina. Fluorescein angiography revealed occlusive retinal vasculitis, while optical coherence tomography showed paracentral acute middle maculopathy (PAMM) in the OD. A thorough systemic evaluation revealed hyperhomocysteinemia and a positive Mantoux test. A diagnosis of PAMM with occlusive retinal vasculitis in presumed intraocular tuberculosis and hyperhomocysteinemia was made. Retinal vasculitis improved with oral corticosteroid, intravitreal anti-vascular endothelial growth factor and laser photocoagulation. However, the patient declined antitubercular therapy despite recommendations. This unique report indicates that PAMM may complicate tubercular retinal vasculitis, especially in the presence of systemic hypercoagulable states.